ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒæ•™è‚²å¦é™¢æ±‰è¯ä¸“ä¸š2015å±Šå¦ç”Ÿçš„æ±‰å—ç¬”ç”»å’Œç¬”é¡ºåè¯¯åˆ†æž - Salsabiila, Salsabiila (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractLearning Chinese inseparable its writing symbols, that is the Chinese characters. Chinese characters are symbols used to write the Chinese language, is the carrier of Chinese history and culture heritage. But in the process of learning Chinese, there are students still have not mastered the skills to write Chinese characters, especially strokes and order of strokes of Chinese characters. Strokes or ?bi hua? are small structure of Chinese charactes, and order of strokes or ?bi shun? are the order of writing Chinese characters. Writing Chinese characters should be based on the stroke and order of strokes Chinese characters, all have a fixed order, cannot be scribbled. This research about the errors of stroke and order of strokes Chinese characters and focuses to the student on year 2015 Chinese study of Tanjungpura University. Based on the research, the writer having a analysis and give some suggestion to the Chinese characters teaching.Keywords: Chinese Characters, Stroke and Order of Stroke, Errors Analysis